Studying Nature In Situ: Immersive Education for Better Integrated Water Management. (March 2013) - Dennison, William; Oliver, Peter
Abstract The term immersive education is currently used in two educational areas – language education, which involves students being totally immersed in a language and its culture; and virtual education, where teachers use computers and simulation games to immerse learners in a virtual, computer‐generated environment that mimics a real‐world environment and allows learners to interact with it. This paper uses examples from university teaching practices in marine studies and coastal zone management to make a case for a third definition for immersive education in tertiary settings – educating water managers by immersing and guiding them through real‐world situations that involve understanding and managing water, biodiversity, catchments, and people, and the interactions between them. Immersive education of this third kind, and traditional tertiary education approaches such as lectures and demonstrations, are compared, and the advantages of immersive education are discussed. The examples from practice and discussion presented show immersive education as being experiential and real, process‐driven, trans‐disciplinary, collaborative, participatory, and active, encouraging critical thinking and a renegotiation of power in relationships between participants. Such immersive education develops passion and persuasive capacity in students, providing personal experiences that are memorable and potentially life‐changing. Challenges to immersive education in tertiary education, including lack of finances, teacher burn‐out, safety concerns, and inertia to maintain the status quo of traditional education, are highlighted, as are ways to overcome these.